Technology and domestic and family violence: victimisation, perpetration and responses - Harris, Bridget A. (Routledge studies in crime and society, 2023)
"This book brings together academics and advocates to explore an emerging issue: the use of technology by perpetrators of domestic and family violence. Of interest too, is critique of government and non-government activities in this arena and, how technology can be harnessed to respond to harm. Domestic and family violence (DFV) is widely recognised as an important social issue, impacting the safety and wellbeing of victim/survivors and their children, and on a broader scale, threatening risk, and security on global levels. This book provides insights drawn from research and practice in the Global South and Global North to provide an evidence base and real-world solutions and initiatives to understand, address and ultimately prevent, technology-facilitated domestic and family violence and how technology can be used to effect positive change and empower victim/survivors and communities. Technology and Domestic and Family Violence will be of great interest to students and scholars on victimology, criminology, social work, law, women's studies, sociology and media studies. It will also be a valuable reference for practitioners, government and non-government advocates working on issues around domestic violence"--